Presupuesto del Gobierno Autónomo Descentralizado Municipal del cantón Vinces en el periodo 2023. - Borja Solís, Joselin Anahis (2025)
This study focuses on analyzing the 2023 budget of the Autonomous Decentralized Municipal Government of the Vinces Canton, with the aim of evaluating its accounting management and verifying compliance with applicable financial regulations. Using a mixed approach that combines qualitative and quantitative methods, key accounting instruments such as the trial balance, budget execution statement, and financial position statement were examined. Among the main findings, the coherence of accounting records stands out, as evidenced in the trial balance, which shows an increase in current revenues and total assets, reflecting a financially responsible administration. Likewise, the budget execution statement revealed an adequate alignment between initial planning and actual execution. Finally, financial indicators show that the executed budget was focused on investment, benefiting the canton’s development. However, long-term infrastructure investment was limited, which could compromise operational sustainability in the future. This suggests the need to optimize budget allocations to improve resource efficiency. Based on the results, specific recommendations are proposed, such as refining budget projections, implementing periodic audits, and strengthening the use of technologies to ensure the consistency of accounting reports. These measures aim to promote a more efficient and reliable administration focused on benefiting the community.